(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chitra Banerjee Divakaruni is an Indo-American writer whose main concern is to write novels in a mixture of cultural and mythical traditional ways. She presents her works with mysterious narration in a world that engages the human‟s curious mind to discover the unknown world of myth. The psychological myth teaches, shapes, and guides human life. Like many women writers, Chitra Banerjee creates memorable characters in her novels, and through the character‟s narration, women can understand how they are enacted in their difficult situations.